Myths and Ecological Awareness of the Riau Archipelago Society in the Short Story “Commander of the Sea” by Abdul Kadir Ibrahim - Tessa Dwi Leoni (International Conference on Science, Education, and Technology, 2023)
The maritime tradition in the life of the people of the Riau Archipelago is known to be very strong. To find out about this maritime tradition, it is necessary to study the works of fiction written by writers from the Riau Archipelago, namely Abdul Kadir Ibrahim. In one of his works of fiction entitled “Panglima Laut”, AKIB is very good at narrating the stories of the life of the coastal community and the myths that are still developing in the life of the Malay community from ancient times to the present. Myths related to cats, the sea, and fishing will be the focus of this study. When examined further, it is evident that these myths lead to efforts to preserve the natural environment. This also certainly can prove how the ecological awareness of the community towards the environment. Data obtained through heuristic reading and recording techniques. Furthermore, the data were analyzed using descriptive qualitative method which refers to ecocritical theory.